Voting on the threat of exclusion in a public goods experiment - Astrid Dannenberg; Corina Haita-Falah; Sonja Zitzelsberger (Philipps-University Marburg, School of Business and Economics, 2019)
Ostracism is practiced by virtually all societies around the world as a means of enforcing cooperation and excluding members who show anti-social behaviors or attitudes. In this paper, we use a public goods experiment to study whether groups choose to implement an institution that allows for the exclusion of members. We distinguish between a costless exclusion institution and a costly exclusion institution that, if chosen, reduces the endowment of all players. We also provide a comparison with an exclusion institution that is exogenously imposed upon groups. A significant share of the experimental groups choose the exclusion institution, even when it comes at a cost, and the support for the institution increases over time. Average contributions to the public good are significantly higher when the exclusion option is available, not only because low contributors are excluded but also because high contributors sustain a higher cooperation level under the exclusion institution. Subjects who vote in favor of the exclusion institution contribute more than those who vote against it, but only when the institution is implemented. These results are largely inconsistent with standard economic theory but can be better explained by assuming heterogeneous groups in which some players have selfish and others have social preferences.
Keywords: C72; C91; C92; D02; D71; H41; 330; public goods experiment; cooperation; ostracism; institutional choice; social preferences